(untitled) (Global Journal of Medical Research, 2014)
This is a preliminary study utilizing drug targeting approach for developing sildenafil citrate (SFC) pulmonary delivery system, a first -line for pulmonary arterial hypertension (PAH) treatment and hence reducing the dose and the side effects. The closed melt method was employed for preparing SFC -solid lipid microparticles dispersions (SFC -SLMDs), a nonsolvent technique aid in the production of drug -matrix dispersions with sustained release properties. Glyceryl behenate (GB) (Compritol® 888 ATO) was used as the retarding matrix and the results shown that as its ratio increase there was a decrease in the fine particle fraction, an increase in the drug content and a prolong drug release pattern. The best model fit the release data was Higuchi -Matrix model which indicates drug diffusion -controlled releasing mechanism. Thus, inhaled SFC -SLMDs dry powder will improve PAH treatment via drug localization at low doses and reducing the administration frequency.